Innovation Diaper “Pa Teaw Sai Deaw” in Preterm Infant - หะยีเซะ วนิสา; ดำคล้าย วิมลวรรณ; มนุกูล ลาตีฟาร์ (Princess of Naradhiwas University Journal, 2018)
The purpose of this one group pretest posttest design in quasi-experimental research is to compare between before and after the effectiveness and expenses of innovation diaper “Pa teaw sai deaw”. Purposive sampling was used to recruit the sample, which included 25 of nurse in NICU of Naradhiwasrajanagarindra Hospital. Preterm Infants used innovation diaper “Pa teaw sai deaw” which developed by researcher, verified and edited by 3 experts. And Research instruments consisted of the demographic questionnaire with its Cronbach’s alpha coefficient’ reliability was 0.86. Data were analyzed by using descriptive statistics and t-test. The results of this study. Mean score of effectiveness after used innovation diaper “Pa teaw sai deaw” was significantly higher than Cloth diaper (t = 23.97, p< 0.05) and mean Expenses (Bath) per day after used innovation diaper “Pa teaw sai deaw was significantly less than diapers (t = 21.16, p < 0.05). These findings suggest that the innovation diaper “Pa teaw sai deaw” was effective. Nurse should this innovation for applyingto nursing care and reduces preterm infant care costs.